As experiências turísticas no patrimônio cultural: uma análise do passeio a pé no Centro Histórico de São Luís - CARVALHO, Concilene Régia Nascimento Campos de (2022)
The study aims to analyze whether the dimensions of the tourist experience are represented in the Passeio a Pé in the Historic Center of São Luís, based on the perception experienced by the “participants” and/or “tourists”. It presents the theoretical and conceptual basis of Cultural Heritage and the interfaces with memory and tourism. It addresses concepts that link experience, tourist experiences and experiential tourism. Analyzes tourist experiences in tourism products and services. Discusses the tourist experience and experience tourism. It addresses the historical aspects of São Luís and characterizes the walking tour in the Historic Center of São Luís. It is an exploratory and descriptive study with a qualitative character, with semi-structured interviews and a visual record of the investigated spaces, with a theoretical, critical, dialectical and interdisciplinary model about the walking tour in the Historic Center of São Luís, Maranhão, using bibliographic research and documentary. This phase of the research was carried out through consultations in books, theses banks, dissertations and scientific articles, with emphasis on relevant authors such as: Halbwachs (2006), Nora (1993), Choay (2006), Horta, Grunberg and Monteiro (1999 ), Trigo (2010), Benjamin (1989), Alexandre Panosso Netto (2010; 2011), Pine II & Gilmore (1999) and Oh, Fiore and Jeong (2007), Beni (2006). Such theoretical references permeated the entire research corpus. It describes the methodological path that guided the development of this investigation. The type of research, the place where the investigation was carried out, the participants are detailed, as well as the data collection instruments, collection procedures and analysis of results. It concludes that the walking tour in the Historic Center of São Luís broadens the view of its participants to the cultural heritage of the city, envisioning its preservation and resignification, as well as triggering their sensations and feelings that can generate memorable tourist experiences.